The good bank: preference of banking institutions based on perceptions of corporate environmental and social causes - Gaspar, Augusta D.; Pinto, Joana Carneiro (Frontiers in Behavioral Economics, 2024)
The Good Bank:This study aims to contribute to understanding factors that explain consumer's preferences among different banks, exploring the roles of Corporate Social Responsibility (CSR) targeted primarily at Environmental causes and secondarily at Social causes, on corporate image (CI), consumer satisfaction (CS) and consumer loyalty (CL). We tested whether integrating a CSR description with environmental causes into the bank marketing strategy would positively affect CI, CS and CL. We also inspected the effect of online banking vs direct human contact, and perception of price fairness, as well as that of the consumers' demographic variables. A survey was carried out online, with 322 international respondents randomly assigned to evaluate one of eight different bank conditions. Results indicated that only the CSR description and the perception of price fairness were critical in the respondents' CI, CS and CL. We conclude that businesses in the banking sector enhance their global reputation when investing in environmental CSR.